Evaluación de impactos ambientales generados durante las etapas de uso y disposición de los residuos de las toalllas higiénicas y copas mestruales. (2018)
The female population experiences one of the most physiological processes month after month controversies of his life, since they all have and live differently each of menstrual cycles, while some see it as a wonderful gift from the nature, others suffer and want their menstruation not come, among other things because they are terrified of having to bleed. Regardless of each experience, the reality is that over time the industry has taken care of manufacture all kinds of products such as: sanitary towels, tampons, cups menstrual, menstrual discs, reusable pads, waterproof pantyhose, etc., some more popular than others but all manufactured with the same purpose; make of those red days "days without stains on clothes". Regarding the previous: We have put to think about the environmental impact generated by these products? Do we know with certainty that synthetic compounds and toxic agents are used during the manufacture of same? It seems that yes but the scenario is different. During the development of this work, hygienic towels and glasses were chosen menstrual cycles in order to compare the environmental impacts generated by the use and the disposition of these two (2) products and thus determine the level of contamination through a qualitative and quantitative analysis of each of the products. The adopted methodology for the identification and evaluation of the impacts is based on the methodology Conesa (1997). For which, analyzes of laboratory to evaluate some physicochemical parameters to two (2) blood samples menstrual cycle and the amount of solid waste generated by the use was determined of each of these products taking into account a population sample. As result, the quality of the disposed liquid waste ie the blood was determined menstrual and possible impacts on biotic, abiotic and partner media were identified economic, also taking into account recent studies that share that the body human can accumulate compounds such as benzophenones (BP) and parabens (PB) (agents that are used during the formulation of several products for the care personal) and that were found in the menstrual blood.